Estudio del proceso de educación continua bajo la norma ISO 21001:2018 en la ESPAM MFL - Murillo Moreira, Karla Valentina (2024)
The primary objective of this research was to apply the ISO 21001:2018 standard approach to the Continuing Education process at ESPAM MFL to contribute to the fulfillment of certification requirements. An exploratory descriptive research type with a qualitative approach was applied, along with inductive, deductive, and synthetic analytical methods. The research was developed in four stages: gathering relevant information, characterizing the Continuing Education process, analyzing the risks and opportunities of the process, and establishing process record formats. Research tools such as the process characterization form, performance indicator form, FMEA matrix, and Bizagi modeler were used. The main results determined that the Continuing Education department has a process linked to the institutional macro-processes of teaching. Additionally, the performance indicator formulation showed a performance percentage of 71.17%. The analysis of risks and opportunities identified two high-risk factors in the Continuing Education process. Finally, fourteen formats were established to carry out process records, which were schematically modeled using the Bizagi tool.